Analisis Strategi Pengembangan Produk Berdasarkan Matrix Ansoff pada Panglong Hans Barokah Aceh Tenggara - Jihan Abiah Rahmah; Khafi Puddin; Fadli Agus Triansyah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of digital marketing has encouraged business actors to adapt their marketing and product development strategies to enhance competitiveness. However, not all businesses are able to effectively optimize the use of digital technology, particularly those with specific consumer characteristics. This study aims to analyze product development strategies based on the Ansoff Matrix at Panglong Hans Barokah in Southeast Aceh and to examine the role of digital marketing in supporting business development. This research employs a qualitative approach using a case study method, with data collected through observation, interviews, and documentation. Data analysis was conducted using a descriptive qualitative approach, including data reduction, data display, and conclusion drawing. The findings indicate that the business strategy implemented tends to align with the product development strategy, as reflected in the creation of more modern door designs based on consumer preferences. On the other hand, the utilization of digital marketing has not been optimal due to a mismatch between the selected platforms and customer characteristics, where WhatsApp is more effective than Instagram in facilitating communication and transactions. These findings suggest that business success is not solely determined by technological adoption, but also by the ability to align strategies with consumer behavior. The implications of this study highlight the importance of aligning product development strategies with appropriate digital media selection to improve marketing effectiveness and business competitiveness.